Economic and environmental impacts of a carbon adder in New York - Gökçe Akın-Olçum; Christoph Böhringer; Thomas F. Rutherford; Andrew Schreiber (University of Oldenburg, Department of Economics, 2019)
New York is considering additional emission regulation on top of its obligations under the Regional Greenhouse Gas Initiative (RGGI) to achieve its State Energy Plan targets. The proposed measure is a so-called "carbon adder" on CO2 emissions from the power sector which is set as the difference between the targeted social cost of carbon and the prevailing RGGI price for CO2 emission allowances. We investigate the potential economic and environmental impacts from the imposition of a carbon adder on New York's power sector. While our analysis indicates the risk of excess cost through overlapping regulations, we find that the carbon adder gives the "right" price signal for New York's power generation to turn into a greener one. Market requirements for permit price floors in the RGGI market induces carbon permit retirements across RGGI states leading to small reductions in region- and country-wide emissions levels.
Keywords: D61; H21; H22; Q58; 330; environmental regulation; overlapping regulation; emission taxes; emissions trading